PEMANFAATAN EKONOMI DIGITALISASI DI LINGKUNGAN MASYARAKAT DESA OMBE BARU - Febrianti, Sri Ayu; Faezal, Faezal; Nurjanah, Titik; Nurmurkamilana, Nurmurkamilana; Syaputri, Dira Irianti Renata (LPPM Institut Pendidikan Nusantara Global, 2022)
Community service is carried out in Ombre Baru Village with the aim of providing an understanding of the use of the digitalization economy in increasing sales of Ombre Baru community products and an understanding of the use of digital marketing in marketing. The method used is the lecture method and question and answer activities. The result of this community service activity is that youth and the community will be able to increase sales through the use of digital marketing, for example through marketplaces and other social media.